Limits of Competition in Special Procedures with an Urgent and Rapid Pattern in the Field of Public Transactions - Achache, Hamza; Khadri, Hamza (Journal of Legal Studies and Researches, 2021)
This study aims to show the extent to which the principle of competition is reflected in the special procedures stipulated in articles 12 and 23 of the regulation of public transactions in force related to urgent transactions that require speed in decision-making, where we noted the lack of dedication of competition in this type of transaction, due to the desire of the legislator to maintain the functioning of public facilities and provide them for service in various circumstances.